SWOT Analysis of Implementation of the Covid-19 Vaccination Policy in Samarinda City - Muksin Muksin; Nur Asiza; Muhammad Henry Gunawan (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2021)
City of Samarinda is the capital of the province of East Kalimantan with the highest performance of COVID-19 vaccination in East Alimantan. On September 30, 2021, for all first-dose vaccination programs, 75% were given and the proportion of vaccine recipients was 66% with Samarinda KTPs. Then for the second dose 40% of vaccine recipients, 32%. The purpose of this study was to analyze the implementation of the COVID- 19 vaccination policy in Samarinda City using a SWOT analysis to find out the strengths, weaknesses, opportunities and threats faced by the Samarinda City government. The data used are secondary data in the form of vaccination policies obtained through the government's official website and news related to the implementation of vaccinations in Samarinda City which will be published in serial electronic media. The results obtained are cooperation with various parties